Health Sciences 2019
DOI: 10.35988/sm-hs.2019.072
|View full text |Cite
|
Sign up to set email alerts
|

Jaunų Žmonių Savižudybių Fenomeno Diskursas

Abstract: Lietuva jau keletą metų yra tarp šalių, kurios lyderiauja pagal savižudybių skaičių Europoje ir pasaulyje. Sаvižudybė – vienа pаgrindinių jаunų žmonių mirties priežаsčių mūsų planetoje. Jauno žmogaus gyvenime kyla daug iššūkių, kurie lemia jaunimo elgsenos kaitą. Šio darbo tikslas buvo jaunų žmonių savižudybių fenomeno analizė. Taikyta sisteminė mokslinės literatūros bei dokumentų apžvalga ir analizė.Sаvižudybė – tаi ne ligа, o desperаtiškas jauno žmogаus, nerаdusio kitos išeities, poelgis. Savižudybė dažniaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…However, it was found that almost one-third of the participants still skip breakfast daily. Other scientific studies from our country indicate that a considerable proportion of children still skip breakfast daily [25][26][27][28][29], but our surveillance study shows that over the years the situation has been improving. The European COSI average of children eating breakfast every day was 75% in 2018-2020.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, it was found that almost one-third of the participants still skip breakfast daily. Other scientific studies from our country indicate that a considerable proportion of children still skip breakfast daily [25][26][27][28][29], but our surveillance study shows that over the years the situation has been improving. The European COSI average of children eating breakfast every day was 75% in 2018-2020.…”
Section: Discussionmentioning
confidence: 67%
“…Although the consumption of fruits and vegetables significantly increased in 2023 compared to 2008, according to the results of the surveillance study, still less than half of our first-grade children consume vegetables and fruits daily. The problem of insufficient consumption of vegetables, fruits, and berries has been pointed out by other Lithuanian scientists as well [ 25 , 26 , 27 , 28 , 29 ]. Comparing the 2018–2020 results from other European countries, the proportion of children consuming fruit and vegetables daily was highest in Portugal, Ireland, and Denmark (≥60% and 57%) and lowest in Georgia, Spain, and Latvia (23%, 27%, and 13%, respectively); the proportion of Lithuanian children consuming fruit and vegetables every day was 32% and 27%, respectively, in the fifth round [ 12 ] and more than two-fifths in 2023.…”
Section: Discussionmentioning
confidence: 99%
“…This argument is corroborated by the research that about one-third of school children are injured during physical education classes, with boys being injured more often than girls. Injuries were most common in grades 6 to 8, with basketball and soccer being the main culprits for boys and volleyball for girls (Strukčinskienė et al, 2015). Injury aid and treatment is very important to learn both for the community, educators and students as one of the first aid, but a lot of community educators and students who face someone getting injured just screaming for help and fear (Pasaribu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%